Efforts to Improve the Quality of Early Childhood Education - Nurul Fahimah; Shinta Mutiara Puspita; Eko Sulistiono (Universitas Muhammadiyah Enrekang, 2024)
This research is motivated by the fact that PAUD teachers are required to have competencies that include pedagogical, personal, professional, and social to support children's development optimally. Teachers play an important role in efforts to develop their students' motor skills, so that children become individuals who develop according to their development and are more independent. The aim of this research is to determine efforts to improve the quality of early childhood education. This research uses a qualitative research design, this research involves PAUD teachers as resource persons. Based on the research results, it shows that teacher competence is a determining factor in teacher success in carrying out their duties to facilitate children's development. The four teacher competencies (professional, pedagogical, personality and social competencies) must always be developed and improved to maintain the quality and improve the quality of learning activities in schools. Support from various parties is important in the process of increasing teacher competency.